Microrganismos endofíticos e associados de melancia e aplicação biotecnológica - Ishizawa, Taís Aragão (Universidade Federal do Tocantins, 2017)
Endophytic microorganisms have been studied in the identification of new species and for their importante in biotechnological applications. Can be isolated them from seeds, roots, leaves and in fruits of several plant species. Besides, the relation between these microorganisms and watermelon leaves and fruits is far from being well known. Therefore, the main of this work was to identify both endophytic and associated bacteria and yeasts to leaves and fruits of watermelon, as well as evaluate biotechnological potential applications of yeast isolate. The samples were obtained of fruits from Brasília-DF and plants from Formoso do Araguaia-TO. For the isolation of the microorganisms were used different procedures for the leaves: fragmentation and crushing, by testing four surface disinfection conditions and for the fruits: crushing, enriching and filtration in membrane. Molecular identification and characterization was realized by the colony PCR technique for bacteria and the extraction of genomic DNA from yeasts and bactéria. The DNAs of the isolates was amplified using oligonucleotides P027F and R1357 for bacteria and NL1 and NL4 for yeast. For the yeasts isolate tests of antagonisms for phytopathogenic and producers of indoleacetic acid (AIA) were carried out. A total of 380 bacteria and 243 endophytic and associated yeasts were isolated, obtaining a higher number of isolates from the watermelon leaf tissue and 71 bacteria and 92 yeasts were identified. Twelve genus of bacterias were identified, with the gener Pantoea sp. isolated in larger quantity. For yeasts isolated were identified five genus, with featured for the specie Sporidiobolus pararoseus obtained of leaves and fruits of watermelon. Associated yeasts isolates TAIL 04 (99% Saccharomyces cerevisiae) and TAIL 63 (99% Pseudozyma Antarctica) showed antagonistic activity for the fungi Sclerotinia sclerotirum, Alternaria sp., Curvularia lunata, Rhizoctonia sp., Didymella sp. and Pyricularia oryzae. This also was inhibied by TAIL 95 (99% Hannaella sinensis) and TAIL 66 (100% Sporidiobolus pararoseus) isolated and showed greater inhibition of 32,82% with S. cerevisiae (TAIL 04). Simultaneously, S. cerevisiae (TAIL 04) and P. Antarctica (TAIL 63) showed capacity to producer indoleacetic acid (IAA) in concentrations of 21,14 μg/mL and 15,79 μg/mL, respectively, in 7 days of incubation. It is concluded that watermelon leaves and fruits have importants endophytics and associated bacterias and yeasts of biotechnological interest as grownth promoters and antagonistics, making possible their use in the development of bioproducts.